1983
DOI: 10.1128/iai.40.1.46-55.1983
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between in vivo and in vitro studies of modulation of resistance to experimental Candida albicans infection by cyclophosphamide in mice

Abstract: Mice receiving a single injection of cyclophosphamide (150 mg/kg) 1 to 6 days before inoculation with viable Candida albicans showed an increased susceptibility to the challenge accompanied by a reduction in peripheral blood polymorphonuclear leukocytes and lymphocytes as well as in spleen cellularity. Several immunological in vitro functions also appeared to be dramatically depressed. Most of these hematological and functional parameters returned to control values by day 9 after cyclophosphamide administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Studies using murine models of disseminated candidiasis have demonstrated that macrophages play an important role in host resistance [12–14]. Macrophages are phagocytic cells of the immune system that are able to recognise and eliminate microorganisms crossing the epithelial barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using murine models of disseminated candidiasis have demonstrated that macrophages play an important role in host resistance [12–14]. Macrophages are phagocytic cells of the immune system that are able to recognise and eliminate microorganisms crossing the epithelial barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Although the importance of T-cell-dependent immunity in chronic mucocutaneous candidosis has been clearly established (12,29,34,50), the protective role of this component of immunity in systemic candidosis has not been so well defined (13,23,46). As a matter of fact, innate natural immune mechanisms appear to be most important in resistance to disseminated C. albicans infections, with a major role apparently being played by nonspecifically activated polymorphonuclear leukocytes (PMN) (2,6,23,33,47) and macrophages (1,3,5,30,43).…”
mentioning
confidence: 99%
“…For the past few years our group has been studying systemic acute C. albicans infections in normal and immunomodulated mice (4,8). In this particular model of systemic challenge, the role played by the natural defense mechanisms in reducing the invading pathogenic burden seems to be decisive.…”
mentioning
confidence: 99%